In situ growth of amorphous vanadium oxide nanospheres on carbon cloth as free-standing cathodes used in high performance aqueous zinc-ion batteries. Issue 7 (15th March 2023) - Han, Xuguang; Zhang, Yan; Liu, Mengmeng; Sun, Yifei; Gou, Wenshan; Xu, Zhao; Li, Chang Ming
Abstract : 3D amorphous VO x microspheres were in situ grown on alkali-treated carbon cloth (VO x MSs@ACC) as cathodes for AZIBs. VO x MSs@ACC cathodes show excellent specific capacity and cycling performance due to rich active sites and fast ion transport rates. Abstract : Vanadium oxide with abundant interchangeable oxidation states and a variety of different crystal structures is considered to be the most promising Zn-ion host material for high-performance aqueous zinc-ion batteries (AZIBs). Nevertheless, certain constraints, including poor reversibility, low intrinsic conductivity, sluggish electrochemical kinetics, low density of exposed active sites, and low actual capacity of the material, limit their performance in AZIBs. In this work, we in situ grew 3D amorphous mixed-valence VO x microspheres on alkali-treated carbon cloth (VO x MSs@ACC) as cathodes for AZIBs. In comparison with a VO x MSs powder-constructed cathode, VO x MSs@ACC cathodes exhibit higher specific capacity (1.79 mA h cm −2 at 2.7 A m −2 ) and longer cycling performance over 2500 cycles mainly due to their faster ion transport rates, abundant ion storage sites and more effective easing of volume expansion. This work thus sheds light on the design of free-standing vanadium-based cathodes for AZIBs.